Heterozygous Mutation in IκBNS Leads to Reduced Levels of Natural IgM Antibodies and Impaired Responses to T-Independent Type 2 Antigens - Pedersen, Gabriel K.; Ádori, Monika; Stark, Julian M.; Khoenkhoen, Sharesta; Arnold, Carrie; Beutler, Bruce; Karlsson Hedestam, Gunilla B. (Frontiers in Immunology, 2016)
Mice deficient in central components of classical NF-κB signaling have low levels of circulating natural IgM antibodies and fail to respond to immunization with T-independent type 2 (TI-2) antigens. A plausible explanation for these defects is the severely reduced numbers of B-1 and marginal zone B (MZB) cells in such mice. By using an ENU mutagenesis screen, we identified a role for the atypical IκB protein IκBNS in humoral immunity. IκBNS deficient mice lack B-1 cells and have severely reduced numbers of MZB cells and thus resemble several other strains with defects in classical NF-κB signaling. We analyzed mice heterozygous for the identified IκBNS mutation and demonstrate that these mice have an intermediary phenotype in terms of levels of circulating IgM antibodies and responses to TI-2 antigens. However, in contrast to mice that are homozygous for the IκBNS mutation, the heterozygous mice had normal frequencies of B-1 and MZB cells. These results suggest that there is a requirement for IκBNS expression from two functional alleles for maintaining normal levels of circulating natural IgM antibodies and responses to TI-2 antigens.